Nucleome programming is required for the foundation of totipotency in mammalian germline development. (15th June 2022) - Nagano, Masahiro; Hu, Bo; Yokobayashi, Shihori; Yamamura, Akitoshi; Umemura, Fumiya; Coradin, Mariel; Ohta, Hiroshi; Yabuta, Yukihiro; Ishikura, Yukiko; Okamoto, Ikuhiro; Ikeda, Hiroki; Kawahira, Naofumi; et al.
Abstract: Germ cells are unique in engendering totipotency, yet the mechanisms underlying this capacity remain elusive. Here, we perform comprehensive and in‐depth nucleome analysis of mouse germ‐cell development in vitro, encompassing pluripotent precursors, primordial germ cells (PGCs) before and after epigenetic reprogramming, and spermatogonia/spermatogonial stem cells (SSCs). Although epigenetic reprogramming, including genome‐wide DNA de‐methylation, creates broadly open chromatin with abundant enhancer‐like signatures, the augmented chromatin insulation safeguards transcriptional fidelity. These insulatory constraints are then erased en masse for spermatogonial development. Notably, despite distinguishing epigenetic programming, including global DNA re‐methylation, the PGCs‐to‐spermatogonia/SSCs development entails further euchromatization. This accompanies substantial erasure of lamina‐associated domains, generating spermatogonia/SSCs with a minimal peripheral attachment of chromatin except for pericentromeres—an architecture conserved in primates. Accordingly, faulty nucleome maturation, including persistent insulation and improper euchromatization, leads to impaired spermatogenic potential. Given that PGCs after epigenetic reprogramming serve as oogenic progenitors as well, our findings elucidate a principle for the nucleome programming that creates gametogenic progenitors in both sexes, defining a basis for nuclear totipotency. Synopsis: Multi‐omics profiling of an in vitro system for mouse germ‐cell development delineates key principles of nucleome programming, including progressive euchromatization and dynamic insulation, as a basis for nuclear totipotency. 3D genome matures unidirectionally over epigenetic reprogramming and programming. Epigenetic reprogramming creates broadly open chromatin with enhanced insulation. Spermatogonia show minimal, peripherally‐positioned, and pericentromeric LADs. Nucleome mis‐programming leads to impaired spermatogenic potential. Abstract : Progressive euchromatization and insulation dynamics safeguard nuclear totipotency during gametogenesis.